COVID-19 Vaccine–Related Beliefs and Behaviors Among Patients With and Survivors of Hematologic Malignancies. Issue 2 (9th February 2023) - Akesson, Jesper; Weiss, Elisa S.; Sae-Hau, Maria; Gracia, Gabriela; Lee, Marialanna; Culp, Lucy; Connell, Brian; Butterfield, Steve; Conti, Rena M.
Abstract : PURPOSE: Patients with and survivors of hematologic malignancies are particularly vulnerable to COVID-19 disease and complications. This study examined patients' vaccination attitudes and behaviors and their correlates. METHODS: A two-wave survey was fielded in December 2020 and June 2021 among hematologic malignancy patients and survivors (N = 2, 272). Demographic characteristics, intent to get vaccinated, vaccination status, attitudes toward vaccination, and level of trust in specific sources of information about COVID-19 vaccines were assessed. Descriptive statistics were calculated, and linear probability models were estimated to examine binary outcomes and their correlates. RESULTS: In December 2020, before COVID-19 vaccines were available, 73% stated they were likely or very likely to get vaccinated if an FDA-approved vaccine became available; however, in June 2021 over 90% reported being vaccinated. Being younger, unmarried, trusting local faith leaders, and not having a bachelor's degree or more were negatively associated with getting vaccinated. Among those hesitant in December 2020, those who expressed a distrust of vaccines in general were least likely to get vaccinated. Being vaccinated in June 2021 was positively associated with the degree to which respondents trust their oncologist, federal agencies, and pharmaceutical companies. Oncologists and primary care physicians were reported as the most trusted sources for information about vaccines. DISCUSSION: COVID-19 vaccine hesitancy remains a public policy concern even now, as additional boosters are recommended among vulnerable populations. Our findings suggest that patient trust in their treating physicians can play a critical role in promoting individual patient and public health goals.